Migration Shaping Musical Careers: The Experiences of Women Artists encountered in Montreal - Marcoux-Gendron, Caroline (Intersections, 2022)
This article explores how migration influences professionalization and gender dynamics in the musical careers of ten women who have lived in Montreal within their migratory journey. Based on qualitative exploratory research, it reveals how migration complicates the notion of professionalization—a concept that is not unequivocal or shared for all musicians. It also shows the multiple mobilities (social, economic, statutory) experienced by these women, who find themselves at the centre of a new set of power relations that only an intersectional approach can help to fully capture. Thus, these artists navigate a multiplicity of sociocultural worlds and must negotiate multilayered, if not multiscale, gender, and professional logics.